2017
DOI: 10.3389/fnagi.2017.00001
|View full text |Cite
|
Sign up to set email alerts
|

Reward Dependent Invigoration Relates to Theta Oscillations and Is Predicted by Dopaminergic Midbrain Integrity in Healthy Elderly

Abstract: Motivation can have invigorating effects on behavior via dopaminergic neuromodulation. While this relationship has mainly been established in theoretical models and studies in younger subjects, the impact of structural declines of the dopaminergic system during healthy aging remains unclear. To investigate this issue, we used electroencephalography (EEG) in healthy young and elderly humans in a reward-learning paradigm. Specifically, scene images were initially encoded by combining them with cues predicting mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
115
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(126 citation statements)
references
References 75 publications
8
115
3
Order By: Relevance
“…A morphology similar to that which we observed in the SR 10 days after ischemia–an elongated rod-shaped nucleus and a body with short processes, is characteristic of rod-shaped microglia [ 55 , 56 , 57 , 58 ]. Rod-shaped microglia have been described in the cortex in rats with diffuse brain injury [ 56 ], in the hippocampus in older adults [ 58 ] and present in experimental models of optic nerve degeneration and in some slowly developing neurodegenerative diseases progressing to dementia [ 55 ].…”
Section: Discussionsupporting
confidence: 77%
“…A morphology similar to that which we observed in the SR 10 days after ischemia–an elongated rod-shaped nucleus and a body with short processes, is characteristic of rod-shaped microglia [ 55 , 56 , 57 , 58 ]. Rod-shaped microglia have been described in the cortex in rats with diffuse brain injury [ 56 ], in the hippocampus in older adults [ 58 ] and present in experimental models of optic nerve degeneration and in some slowly developing neurodegenerative diseases progressing to dementia [ 55 ].…”
Section: Discussionsupporting
confidence: 77%
“…This is exemplified by proteins such as S100B, which is released from astrocytes with neurotrophic or neurotoxic effects on neurons depending on their concentration and on the astrocytic activation state [ 71 , 72 ]. In turn, increased expression and secretion of S100B from astrocytes may be reflected in the CSF patterns as reported in traumatic brain injury [ 73 ], AD [ 74 , 75 ] and sCJD [ 76 ]. Consequently, astrocytes are turning into a potential target for therapeutic intervention in neurodegenerative diseases associated with an inflammatory component [ 77 ], indicating that astrocyte-associated metabolites may be potential biomarkers in biological fluids.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, NF-κB/p65 protein expression level was decreased as opposed to IκBa expression that was increased in BV-2 cells and primary microglia treated with LPS+LiCl. Moreover, the mRNA expression levels of pro-inflammatory cytokines IL-1β, IL-6, TNF-α and iNOS were decreased; on the other hand, the anti-inflammatory cytokine IL-10, a marker for M2 phenotype [ 26 ] was increased. It would appear therefore that IL-10 may be differentially regulated compared with the proinflammatory mediators and that LiCl promotes polarization of microglia from M1 to M2 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the mRNA expression levels of pro-inflammatory cytokines IL-1β, IL-6, TNF-α and iNOS were decreased; on the other hand, the anti-inflammatory cytokine IL-10, a marker for M2 phenotype [ 26 ] was increased. It would appear therefore that IL-10 may be differentially regulated compared with the proinflammatory mediators and that LiCl promotes polarization of microglia from M1 to M2 [ 26 ]. The present results are consistent with Foltz et al [ 27 ] who reported that GSK-3β was able to phosphorylate Notch-1 in vitro , and that NICD has to be phosphorylated by GSK-3β for its translocation to the nucleus [ 28 ].…”
Section: Discussionmentioning
confidence: 99%